Effect of the sol fraction and hydrostatic deformation on the viscoelastic behavior of prestrained highly filled elastomers. Issue 3 (9th May 2012) - Azoug, A.; Constantinescu, A.; Pradeilles‐Duval, R. M.; Vallat, M. F.; Nevière, R.; Haidar, B.
Abstract This study focuses on the relations between the microstructure and the viscoelastic behavior of an industrial solid propellant belonging to the class of highly filled elastomers. Precisely, the study aims at determining the impact on the viscoelastic behavior of the presence of the sol fraction inside the polymer network. The sol fraction is the part of the binder that a good solvent can extract. The solid propellant is swollen to various extents by solutions of plasticizer and polymer molecules. This swelling leads to a hydrostatic deformation of the polymer network, corresponding to an extension or contraction loading for each specimen. Prestrained dynamic mechanical analysis tests, superimposing a small oscillating strain on a prestrain, characterize the viscoelastic behavior. The degree of swelling of the network and the effective filler fraction drive the viscoelastic response. In addition, the mechanical behavior does not depend on the chemical nature of the introduced sol fraction. Moreover, a nonlinear behavior, i.e., an increase in both storage and loss moduli with increasing prestrain, is initiated at low prestrain. This nonlinearity depends on the contraction or extension of the network and could result from particles aligning with prestrain, which is expected in such highly filled materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013